Generation Y - Yarrow, Kit (Henry Stewart Talks, 2009)
The clout and buying power of Gen Y, How Gen Y is fundamentally different from other generations, Age related needs within Gen Y, Generational gender shifts, What Gen Y wants from products and brands, Seven essentials for marketing to Gen Y